2019
DOI: 10.1371/journal.pone.0215242
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing preferred motif choices and distance impacts

Abstract: People’s daily travels are structured and can be expressed as networks. Few studies explore how people organize their daily travels and which behavioral principles result in the choices of specific network types. In this study, we first reconstruct location networks and activity networks for numerous individuals from high-resolution mobile phone positioning data and define frequent networks as motifs. The results suggest that 99.9% of people’s travels can be characterized by a limited set of location-based mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 50 publications
2
14
0
Order By: Relevance
“…Third, these methods usually involve a large number of records. For instance, mobile phone location datasets often contain millions of users and billions of records ( Cao et al, 2019 ; Deville et al, 2014 ). Even an auxiliary dataset, such as travel surveys, could involve tens of thousands of households or hundreds of thousands of users.…”
Section: Related Workmentioning
confidence: 99%
“…Third, these methods usually involve a large number of records. For instance, mobile phone location datasets often contain millions of users and billions of records ( Cao et al, 2019 ; Deville et al, 2014 ). Even an auxiliary dataset, such as travel surveys, could involve tens of thousands of households or hundreds of thousands of users.…”
Section: Related Workmentioning
confidence: 99%
“…For example, Cao et al. (2019) found that the displacement distance affected the choice of spatial mobility motifs. Therefore, further studies should be conducted to address the factors that could have an impact on temporal stay characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…According to the above rules, individual travel networks can be constructed for mobile phone users, and human mobility motifs extracted from these travel networks to uncover the frequent mobility patterns of citizens (Cao et al., 2019).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations